2014
DOI: 10.1111/mpp.12147
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the shikimate pathway genes, aroA and aroB, in virulence, growth and UV tolerance of Burkholderia glumae strain 411gr‐6

Abstract: Burkholderia glumae is the major causal agent of bacterial panicle blight of rice, which is a growing disease problem for rice growers worldwide. In our previous study, some B. glumae strains showed pigmentation phenotypes producing at least two (yellow-green and purple) pigment compounds in casein-peptone-glucose agar medium. The B. glumae strains LSUPB114 and LSUPB116 are pigment-deficient mutant derivatives of the virulent and pigment-proficient strain 411gr-6, having mini-Tn5gus insertions in aroA encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…For instance, the up-regulation of shikimate pathway proteins encoded by aroA and aroK in the strong biofilm former indicates an increased synthesis of aromatic amino acids in the strong biofilm former Ef 63. Certain studies have shown that the production of 5-enolpyruvylshikimate-3-phosphate synthase by aroA can lead to glyphosphate resistance in pathogenic bacteria such as S. aureus and the virulence, growth, and UV tolerance of the plant pathogen Burkholderia glumae (38,49). This suggests that the strong biofilm former Ef 63 can display increased levels of glyphosphate resistance and pathogenesis mechanisms, possibly resulting in higher biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the up-regulation of shikimate pathway proteins encoded by aroA and aroK in the strong biofilm former indicates an increased synthesis of aromatic amino acids in the strong biofilm former Ef 63. Certain studies have shown that the production of 5-enolpyruvylshikimate-3-phosphate synthase by aroA can lead to glyphosphate resistance in pathogenic bacteria such as S. aureus and the virulence, growth, and UV tolerance of the plant pathogen Burkholderia glumae (38,49). This suggests that the strong biofilm former Ef 63 can display increased levels of glyphosphate resistance and pathogenesis mechanisms, possibly resulting in higher biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified abundance of strains of B. glumae including some highly virulent strains that caused 50% to 75% yield reduction [8] [9]. Additionally, it was predicted that the B. glumae strains in different rice-production regions have some undefined differences in their genome and virulence [3].…”
Section: Introductionmentioning
confidence: 99%
“…The production of auxotrophic strains as live attenuated bacterial vaccines is a classic strategy that has proven successful for multiple pathogens including Salmonella Typhi and Shigella [10][11][12][13][14]33]. In this report, we developed rationally defined mutations in the shikimate pathway of F. tularensis, leading to the creation of the Schu S4 mutants ΔaroC, ΔaroD, and ΔaroCΔaroD.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic mutants of the human virulent subspecies tularensis strain Schu S4 lack the functional proteins encoded by FTT0876 c (aroC), FTT0471 (aroD), or both genes. The aro genes encode enzymes of the shikimate pathway and have been mutated to attenuate other Gram-negative bacteria [10,11], including Salmonella [12][13][14][15]. This pathway is responsible for synthesis of aromatic amino acids in plants and microbes; deletion of aro genes has been empirically determined to decrease virulence in other organisms [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation